2016
DOI: 10.1007/s12011-016-0760-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Content in Cord Blood Is Associated with Maternal Age and Parity

Abstract: At childbirth (parturition), zinc (Zn) homeostasis in cord blood (CB) can be affected by a number of factors: Zn in maternal blood, parturition related stress as well as metallothionein (MT). Both Zn and stress are known inducers of MT which is primarily involved in Zn homeostasis. This study analyzed Zn concentration [Zn], in CB components and MT-2A transcription in CB mononuclear cells (MNC) in relation to primiparous and multiparous childbirth. [Zn] in CB (n = 47) plasma, erythrocytes, and MNCs were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In other studies of ours, an association between zinc concentration in serum, AF or umbilical cord blood in pregnant women and their age was not found [ 42 , 43 ]. In opposition to that, Youssof et al [ 44 ] observed significantly higher zinc content in cord blood plasma in older women compared to younger women after delivery.…”
Section: Discussionmentioning
confidence: 92%
“…In other studies of ours, an association between zinc concentration in serum, AF or umbilical cord blood in pregnant women and their age was not found [ 42 , 43 ]. In opposition to that, Youssof et al [ 44 ] observed significantly higher zinc content in cord blood plasma in older women compared to younger women after delivery.…”
Section: Discussionmentioning
confidence: 92%
“…Our study, however, did not confirm these observations. Youssof et al [ 28 ] found that maternal age and parity may influence Zn concentration in cord blood. Authors suggested that multiparous older mothers would require more Zn supplement during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggested that multiparous older mothers would require more Zn supplement during pregnancy. Decreasing Zn concentration with age and parity may be possible associated with catecholamine level in maternal and cord blood which affects Zn status [ 28 ]. In another study, a significant positive correlation between Zn level in cord blood and birth weight was observed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are several studies in the literature showing different concentrations of plasma Zn in pregnant women according to diverse variables: age, parity, pregnancy pathologies or even place of origin. [77][78][79][80] Zn is transported from enterocytes into the maternal blood thanks to ZnT1 and from there it reaches and enters the placenta by means of ZIP proteins, as stated above. 66 Once Zn is in the placenta, it can be bound to MTs or transported to the cord blood through Zn transporters which include ZIP14, ZnT2 and DMT1.…”
Section: Zn and CD Transport In Pregnancy And Lactation Related Tissuesmentioning
confidence: 99%
“…This will result in alterations of fetal homeostasis of Zn, FGR or changes in anthropometric parameters of the newborn with lower than expected values, among other changes. 60,79 When Cd is present in the placenta, it reaches the fetus, although at low concentrations. 72 Studies conducted by Nakamura et al, revealed that rats on the first day of life, present higher concentrations of Cd in their kidneys and liver, indicating that in the fetal life, Cd has been present at least in the last intrauterine period.…”
Section: Zn and CD Transport In Pregnancy And Lactation Related Tissuesmentioning
confidence: 99%